ANALISIS DIMENSI SALURAN DRAINASE TERHADAP DEBIT CURAH HUJAN DI KECAMATAN AMPENAN: Analysis Of Drainage Channel Dimensions On Rainfall Discharge In Ampenan District - Malo, Agata; Aminullah, Aminullah; Yamin, Muhamad (Yayasan Al-Amin Qalbu, 2025)
The purpose of this study was to analyze the drainage channel dimensions in relation to rainfall discharge in Ampenan District. The types of research that can be used in dimensional analysis of drainage channels include descriptive methods and quantitative approaches. The results show that the dimensions of the Ampenan District drainage channel, with a cross-sectional area of ​​2.99 m2 and a flow velocity of 18,609 m3/s, result in the existing or control discharge (QT) of 55,640 m3/s. Meanwhile, rainfall results in a design discharge (QT) of 1,8018 m3/s, so the control discharge is greater than the design discharge (QT < QR), indicating that the channel dimensions are still adequate and can accommodate rainfall.